Metabolomics and lipidomics to identify biomarkers of effect related to exposure to non-dioxin-like polychlorinated biphenyls in pigs. (June 2022) - Hernández-Mesa, Maykel; Narduzzi, Luca; Ouzia, Sadia; Soetart, Nicolas; Jaillardon, Laetitia; Guitton, Yann; Le Bizec, Bruno; Dervilly, Gaud
Abstract: Recent epidemiological studies show that current levels of exposure to polychlorinated biphenyls (PCBs) remain of great concern, as there is still a link between such exposures and the development of chronic environmental diseases. In this sense, most studies have focused on the health effects caused by exposure to dioxin-like PCBs (DL-PCBs), although chemical exposure to non-dioxin-like PCB (NDL-PCB) congeners is more significant. In addition, adverse effects of PCBs have been documented in humans after accidental and massive exposure, but little is known about the effect of chronic exposure to low-dose PCB mixtures. In this work, exposure to Aroclor 1260 (i.e. a commercially available mixture of PCBs consisting primarily of NDL-PCB congeners) in pigs is investigated as new evidence in the risk assessment of NDL-PCBs. This animal model has been selected due to the similarities with human metabolism and to support previous toxicological studies carried out with more frequently used animal models. Dietary exposure doses in the order of few ng/kg body weight (b.w.) per day were applied. As expected, exposure to Aroclor 1260 led to the bioaccumulation of NDL-PCBs in perirenal fat of pigs. Metabolomics and lipidomics have been applied to reveal biomarkers of effect related to Aroclor 1260 exposure, and by extension to NDL-PCB exposure, for 21 days. In the metabolomics analysis, 33 metabolites have been identified (level 1 and 2) as significantly altered by the Aroclor 1260 administration, while in the lipidomics analysis, 39 metabolites were putatively annotated (level 3) and associated with NDL-PCB exposure. These biomarkers are mainly related to the alteration of fatty acid metabolism, glycerophospholipid metabolism and tryptophan-kynurenine pathway. Graphical abstract: Image 1 Highlights: Hazard identification of non-dioxin-like polychlorinated biphenyls has been carried out at dietary exposure doses. Serum samples from pigs exposed to Aroclor 1260 have been investigated by metabolomics and lipidomics. Glycerophosphocoline levels in serum are altered by exposure to Aroclor 1260. Arachidonic acid, linolenic acid, tryptophan, kynurenine, among others, are biomarkers of effect of NDL-PCB exposure. Exposure to NDL-PCBs has been associated with oxidative stress and inflammation according to the biomarkers of effect found.